The effect of various thermochemical methods on the production of biochar and removal of 2-naphthol orange from wastewater - Ergan, Basak Temur; Aydin, Ebubekir Siddik; Gengec, Erhan (Wiley, 2024)
BACKGROUNDThermochemical conversion methods are essential processes frequently used in the production of biochar and the type chosen affects the properties of biochar. In this study, 2-naphthol orange was removed from synthetic wastewater using biochar adsorbents produced from pelletized furniture sawdust by thermochemical techniques (torrefaction, pyrolysis and gasification) at various durations (0.5-5 h) and temperatures (200-900 degrees C).RESULTSThe adsorbent produced via torrefaction at 200 degrees C in 1 h exhibited the best removal performance. For furniture waste biochar (FWB), the optimum conditions for 2-naphthol orange options were initial concentration 35 mg L-1, pH 2.0, contact duration 2 h, agitation speed 200 rpm, temperature 30 degrees C, 1.0 g L-1 of biochar and - 50-mesh biochar size. The Langmuir isotherm and Pseudo-second-order models showed the highest coefficients of determination (R2 = 0.9947 and 0.9978, respectively). The terms of qm (mg g-1) and KL were found to be 230.45 and 0.28, respectively, from the Langmuir isotherm. Conversely, the terms of qe (mg g-1) and k2 [g (mg.min)-1] were found to be 29.27 and 0.00486, respectively, from the pseudo-second-order model. According to the long-stability experiment, the selected adsorbent of 200-1 (biochar from torrefaction) remained more stable after 10 cycles of adsorption.CONCLUSIONIt was found that the torrefaction process provides significant advantages owing to the removal efficiencies of 2-naphthol orange dye and the fact that biochar production is easier and more economical at low temperatures. (c) 2023 Society of Chemical Industry.
Keywords: biochar adsorbent; waste biomass; thermochemical processes; 2-naphthol orange; adsorption kinetics; thermodynamic